Caracterização morfológica de Liophis reginae semilineatus (Wagler, 1824) e Liophis reginae macrosomus (Amaral, 1935), e o status taxonômico de Liophis oligolepis Boulenger, 1905 - COSTA, Robson Gil Neris (Universidade Federal do Pará, 2013)
The Brazilian subspecies of Liophis reginae (Liophis reginae macrosomus and Liophis reginae semilineatus) were analyzed, in order to characterize the two taxa and to verify the validity of Liophis oligolepis, considered a synonym of Liophis regime semilineatus. External morphology, cranial osteology and hemipenis were examined. Based on a MANOVA, significant sexual differences in head and body variables were identified. A discriminant analysis function (DAF) was performed for males and females separately, in order to maximize in a multivariate space the differences between the three previously defined taxa: Liophis reginae semilineatus, Liophis reginae macrosomus, and Liophis oligolepis. The first discriminant component in males separated clearly Liophis reginae semilineatus and Liophis oligolepis, while Liophis reginae semilineatus and Liophis reginae macrosomus separated at the second discriminant component. In females, the first disctiminant component separated Liophis oligolepis from Liophis reginae semilineatus and Liophis reginae macrosomus. When both sexes were analysed together, for the pairs of taxa Liophis oligolepis - Liophis reginae semilineatus, and Liophis reginae semilineatus - Liophis reginae macrosomus, both pairs were separated by the first discriminant component. Since some specimens of Liophis reginae semilineatus and Liophis reginae macrosomus were registered beyond their previous known distribution, a DAF was applied to verify if these specimens grouped within their presumed taxa or geographically. The first possibility occurred, supporting the validity of each taxon and raising the question of their taxonomic status. The hemipenian morphology does not differ between Liophis reginae semilineatus, Liophis reginae oligolepis and Liophis reginae macrosomus. The three taxa present similar skulls, although differences were observed between the parietal bones of Liophis reginae semilineatus and Liophis reginae oligolepts. The validity of Liophis oligolepis was corroborated, based on meristic, morphometric and morphological characters. Future studies will be necessary to test the Liophis reginae semilineatus and Liophis reginae macrosomus status.